Níveis críticos de n-no3 e n-orgânico em pecíolos de tomateiro de crescimento determinado - SAMPAIO, REGYNALDO ARRUDA; FREITAS, JOSÉ DE ARIMATEIA D. DE; YUPANQUI, FREDY FERNANDO R.; FONTES, PAULO C. R.; MARTINEZ, HERMINIA E. P.; PEREIRA, PAULO R. G. (Revista Ceres, 2015)
.